ANALISIS PENGENDALIAN PERSEDIAAN PRODUKSI PADA CV FANARA ABADI - Syardiansah Syardiansah; Muhammad Fuad; Puspita Sari (Universitas Putera Batam, 2020)
This study aims to determine the level of effectiveness of production supplies on CV. Fanara Abadi in Langsa City. This research is a type of quantitative research with research methods using the analysis of the Economic Order Quantity (EOQ). Sources of data in this study are primary and secondary data obtained through observation, literature and documentation on the CV. Fanara Abadi. The calculation of raw material inventory costs in the study is divided into 3, namely the purchase costs, ordering costs and save costs. Purchase costs are determined from the unit price of raw materials purchased multiplied by the quantity of raw materials purchased. Whereas for ordering costs is influenced by administrative costs and unloading wages. For each order the costs incurred are fixed. Based on the results of analysis and calculations using the EOQ method, it was found that EOQ for 2014 obtained raw materials of 3,381 units of foam, 3,286 units of wire and 1,803 units of fabric. In 2015 EOQ obtained foam raw materials of 3,575 units, 3,117 units of wire and 1,807 units of fabric. In 2016 EOQ obtained 3,557 units of raw materials, 3,117 units of wire and 1,717 units of fabric. In 2017 EOQ obtained foam raw materials of 3,096 units, 3,098 units of wire and fabric 1,719 units. From these results it is clear that by using the EOQ method, the CV. Fanara Abadi can be more effective in controlling the production inventory.